Death Reporting Information System at the Camat Office in Manggeng, Aceh Barat Daya District - Putra, Thabrani (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
This study focuses on the development of a more efficient Death Reporting Information System at the Camat Office in Manggeng, Aceh Barat Daya, addressing the challenges of the existing manual system. The main objectives were to streamline data management, reduce errors, and improve report generation. The new system was developed using Visual Basic .NET to automate processes and ensure more accurate, timely data management. The methodology employed included observation, interviews, system analysis, design, testing, and evaluation. During the observation phase, issues such as the lack of a dedicated death data management application and limited access to accurate data were identified. Interviews with staff further confirmed the need for an automated solution to enhance efficiency. The system analysis showed significant flaws in the existing system, including inefficiencies caused by manual data entry. The newly designed system features an intuitive interface, enabling staff to input, process, and generate death reports more effectively. Testing confirmed that the new system significantly reduced processing times, minimized data entry errors, and improved the overall efficiency of death reporting. It also provided real-time access to data, allowing staff to retrieve and process information more quickly. The successful implementation of this system highlights the importance of integrating technology into public administration. Moreover, it emphasizes the need for adequate staff training to ensure successful adoption and effective system usage. The study concludes that technological integration is essential for improving the efficiency, accuracy, and transparency of public sector services.